2007
DOI: 10.1002/bsl.724
|View full text |Cite
|
Sign up to set email alerts
|

Are release recommendations for NGRI acquittees informed by relevant data?

Abstract: We conducted a retrospective review of factors involved in clinical recommendations for release of patients adjudicated not guilty by reason of insanity (NGRI). Medical records from 91 patients in a maximum security forensic hospital who participated in a formal hearing process to determine suitability for release were reviewed. The purpose of the study was twofold: (1) to examine the process involved in day to day clinical decision-making regarding release from a maximum security forensic hospital and (2) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…The present results support increased training for forensic clinicians on empirically valid violence risk factors, and there is some evidence that forensic decisions can be improved (Manguno-Mire, Thompson, Bertman-Pate, Burnett, & Thompson, 2007). Perhaps a database of systematic reviews of forensic research is needed (i.e.…”
Section: General Discussion and Conclusionsupporting
confidence: 51%
“…The present results support increased training for forensic clinicians on empirically valid violence risk factors, and there is some evidence that forensic decisions can be improved (Manguno-Mire, Thompson, Bertman-Pate, Burnett, & Thompson, 2007). Perhaps a database of systematic reviews of forensic research is needed (i.e.…”
Section: General Discussion and Conclusionsupporting
confidence: 51%
“…Univariate analysis of a general linear model was carried out for discharge, co-varying for the HCR-20 total score at the beginning of the period of observation because the HCR-20 measure of dynamic risk is already established as a predictor of success or failure in such discharges [5-8]. Similarly, we tested whether the HCR-20 scores differentiated between those discharged and those not when co-varying for DUNDRUM-3 and DUNDRUM-4 scores.…”
Section: Methodsmentioning
confidence: 99%
“…Doyle at al have also shown that dynamic (“current” and “risk”) items on the HCR-20 significantly improved the accuracy of prediction of violence after discharge from forensic units [7]. It has been shown that factors such as a higher score on PCL-R and a younger age at the time of first criminal offence were significantly related to release recommendations in a group of NGRI patients in the USA [8]. However evidence presented to Criminal Law (Mental Health) Review boards, when recommending a patient for a move to less secure places, consists of more than risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of individuals found NGRI at the Forensic Division of the Eastern Louisiana Mental Health System, over half were diagnosed with schizophrenia, 36% were diagnosed with a substance use disorder, and 28% with a personality disorder. NGRI accused were predominantly male, had a mean age of 41, were unmarried, and the majority had a criminal history, of which 69% involved violent offenses (Manguno-Mire, Thompson, Bertman-Pate, Burnett, & Thompson, 2007). In a follow-up of all forensic patients discharged from the Auckland Regional Forensic Psychiatry Service in New Zealand from 1998 to 2004, the majority were single men with a mean age of 38 years.…”
Section: Forensic Populationsmentioning
confidence: 97%